The Extended Essay as a Research-Based Learning Tool in the International Baccalaureate Program (an Analysis of the UWC Dilijan Experience) - Hakobyan, Arpine («Ալվարդ Օհանջանյան Վառլենի»)
A growing number of international educational institutions have adopted the International Baccalaureate (IB) Programme, within which the Extended Essay serves as a pivotal component for cultivating students’ research competencies, critical thinking, and independent learning skills. The present study examines the structure and implementation of the EE, with particular attention to its application at UWC Dilijan International School, illustrating its contribution to students’ academic development and preparedness for higher education. The purpose of this article is to analyse the structural and procedural dimensions of the Extended Essay, highlighting its principal characteristics, educational functions, and pedagogical value. Furthermore, the article investigates the practical implementation of the EE within the UWC Dilijan context, demonstrating how the Programme facilitates the development of students’ research skills, critical thinking, and autonomy in learning. This analysis also considers the role of the EE in preparing students to meet the academic demands of higher education institutions. Մեծ թվով միջազգային ուսումնական հաստատություններ կիրառում են Միջազգային բակալավրիատի (IB) ծրագիրը, որում ընդլայնված էսսեն (Extended Essay) ծառայում է որպես ուսանողների հետազոտական կարողությունների, քննադատական մտածողության և ինքնուրույն ուսուցման հմտությունների զարգացման հիմնական բաղադրիչ: Սույն հետազոտությունն ուսումնասիրում է ընդլայնված էսսեի կառուցվածքն ու այն գրելու գործընթացը՝ հատուկ ուշադրություն դարձնելով Դիլիջանի «Յու-Դաբլյու-Սի» միջազգային դպրոցում դրա կիրառմանը՝ ցույց տալով ողջ ներդրումը ուսանողների ակադեմիական զարգացման և բարձրագույն կրթություն ստանալու պատրաստակամության գործում։ Все большее число международных учебных заведений принимают программу Международного бакалавриата (IB), в рамках которой расширенное эссе служит ключевым компонентом для развития исследовательских компетенций, критического мышления и навыков самостоятельного обучения у студентов. В настоящем исследовании рассматривается структура и реализация расширенного эссе, с акцентированием внимания к ее применению в Международной школе “Ю Даблю Си” в Дилиджане, демонстрируя ее вклад в академическое развитие учащихся и их готовность к получению высшего образования.
Keywords: Management of Education